Et une phrase... Virginia Woolf, écrire dans l'entre-deux-guerres - Delourme, Chantal (Signes, 2021)
Addressing the thought and the making of the phrase, as the source of Virginia Woolf's writing, is trying to account for what will never be grasped as an object,but will never cease to be heard through its relation to the impossible. In her work, renewed in many ways, the phrase appears at the same time as more than one and like no other. By engaging in this reading, the book distances itself from the various historicizing approaches that in one way or another reify Woolf's writing. It invites us instead to pay subtle attention to the multiple modes of fabrication of the phrase, to the mobility of the voices that weave it, to the pulsation of the tones that transport it, through texts of different genres, where it blurs all boundaries between them. The book also chooses to shed light on a corpus of Virginia Woolf's fiction which is perhaps less well-known. It is aimed at readers of Virginia Woolf's work for whom this passion for letters and literature is called "phrase". Chantal Delourme is Professor Emeritus at the University of Paris Nanterre, where she taught British literature and literary theory. A specialist in modernism and the work of Virginia Woolf, she has published numerous articles and a monograph on To the Lighthouse, entitled Virginia Woolf, To the Lighthouse. Les arabesques du sens (2001).